2019
DOI: 10.3390/nu11112801
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbohydrate Diet Inhibits Different Advanced Glycation End Products in Kidney Depending on Lipid Composition but Causes Adverse Morphological Changes in a Non-Obese Model Mice

Abstract: Low carbohydrate diets (LC diets) have been noted for adverse health effects. In addition, the effect of lipid composition on an LC diet is unclear. In this study, we used an LC diet containing two different lipids, lard (LC group) and medium-chain triglyceride oil (MCT-LC group), to examine the effect of an LC diet in non-obese mice. Male C57BL/6J mice were fed the control diet or one of the experimental diets ad libitum for 13 weeks. Increased renal weight and glomerular hypertrophy, as well as enlargement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…2 Though the precise mechanisms underlying the effectiveness of the KD are not fully elucidated, candidates like reduction of neuronal hyperexcitability through glutamatergic and amyloid-beta (Aβ) inhibition and KD-mediated reduction of oxidative stress, advanced glycation endproducts (AGEs), and neuroinflammation have been suggested to play a critical role. [3][4][5][6][7][8] For example, in AD, Aβ oligomers interfere with glutamate receptors in the synapses and increase the spillover of glutamate, activating glutamate receptors in the extra-synaptic sites, which in turn activate apoptotic and necrotic pathways. 9,10 Preclinical studies provide ample evidence that elevating ketone bodies regulate Aβ levels.…”
Section: Introductionmentioning
confidence: 99%
“…2 Though the precise mechanisms underlying the effectiveness of the KD are not fully elucidated, candidates like reduction of neuronal hyperexcitability through glutamatergic and amyloid-beta (Aβ) inhibition and KD-mediated reduction of oxidative stress, advanced glycation endproducts (AGEs), and neuroinflammation have been suggested to play a critical role. [3][4][5][6][7][8] For example, in AD, Aβ oligomers interfere with glutamate receptors in the synapses and increase the spillover of glutamate, activating glutamate receptors in the extra-synaptic sites, which in turn activate apoptotic and necrotic pathways. 9,10 Preclinical studies provide ample evidence that elevating ketone bodies regulate Aβ levels.…”
Section: Introductionmentioning
confidence: 99%
“…In the kidney, the level of N ε -(carboxymethyl)lysine was significantly lower in the mice fed a lard--based diet. Contrary, the concentration of N ε -(carboxyethyl) lysine was the lowest in the MCT-fed mice [Kaburagi et al, 2019]. This study underlined the importance of diet composition, not only the ratio between fat and other nutrients.…”
Section: Single Electron Transfer (Set) Mixed (Primary Set Secondary ...mentioning
confidence: 56%
“…The composition of low-carbohydrate diets was evaluated in a study by Kaburagi et al [2019]. Diets consisting of lard vs. MCT oil were compared in non-obese mice fed ad libitum for 13 weeks.…”
Section: Single Electron Transfer (Set) Mixed (Primary Set Secondary ...mentioning
confidence: 99%
“…Restricting CHO intake in patients with IR and T2DM to <30% of daily calories improves the level of HbA1C, one of the glycation-derived AGEs [ 102 ]. In another study, CHO restriction was found to reduce AGEs in the kidney [ 103 ].…”
Section: The Detailed Mechanism Of Insulin Resistance Linked To Hyper...mentioning
confidence: 99%